Relationships in Organizations that Lead to Smoothly of Teamwork in Thai-Chinese Joint Venture Business in Retail and Wholesale - Phonthongchaisawat, Wanwisa; Bandoophanit, Thianthip (KKBS Journal of Business Administration and Accountancy, 2020)
This research to study, problems and obstacles in the relationship between members in the organization and analyzing the factors that encourage members of the Thai-Chinese joint venture organization with different cultural backgrounds are smoothly to teamwork. The result to the problems of the relationship between the members of the organization is caused by unclear work patterns, different compensation, work that is not timely and often has an excuse, no clear of organizational-structure-responsibilities for teamwork, owners neglect to create corporate culture, do not have set goals, employees feel insecurity in the company and not trusting others to act on their behalf. Obstacle of the relationship between members in the organization is caused by having different cultures and different of languages, causing an incompatibility. The factors to supporting with members of the Thai-Chinese joint venture organization have cultural differences able to work together smoothly due to administrators need to learn culture.